Understanding Fraction Number Material Relationship with Ability to Work on Mawaris Problems in Mawaris Fiqh Course in Islamic Family Law Study Program (HKI) - Suyud Arif; Amran Amran (ISLAMIKA, 2022)
The purpose of this study was to determine a positive relationship between understanding fractions and the ability to work on Mawaris questions in the Mawaris Fiqh course at the Islamic Family Law Study Program (HKI). This study uses a survey with a correlational approach. The sample in research is students of Islamic Family Law (HKI) at the Ibn Khaldun University, Bogor, which consists of 20 respondents. Collecting data in this study is to use a test in the form of questions that have been declared valid and reliable, then used as a data collection tool to be studied. The results obtained indicate a positive relationship between understanding fractional numbers and the ability to work on Mawaris questions in the Fiqh Mawaris course at the Islamic Family Law Study Program (HKI), the results are shown by the correlation coefficient rxy = 0.588 with the termination coefficient . by 58%, it can be concluded that the ability to work on the Mawaris problem can be from understanding the material of fractions